2008
DOI: 10.1111/j.1755-6686.2008.00029.x
|View full text |Cite
|
Sign up to set email alerts
|

CE: Continuing Education Article PATIENT MANAGEMENT IN CKD STAGES 1 TO 3

Abstract: This is the first article in a two-part Continuing Education (CE) series on the management of patients with Chronic Kidney Disease (CKD). CKD is now recognised as a global public health concern. It has been classified into five stages to assist healthcare professionals to care for patients presenting with this chronic illness. Numerous risk factors are associated with CKD including anaemia, hypertension and cardiovascular risk. Nephrology nurses play an important role in the monitoring and management of these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 17 publications
0
7
0
2
Order By: Relevance
“…The previous CE article on CKD stages 1 to 3 (Murphy et al 2008) identifies that anaemia is a common complication of CKD. The impairment of erythropoietin production in the kidneys leads to anaemia with signs and symptoms including fatigue, general malaise, angina, tachycardia and shortness of breath on exertion, especially in the absence of pulmonary or peripheral oedema.…”
Section: Anaemiamentioning
confidence: 99%
See 1 more Smart Citation
“…The previous CE article on CKD stages 1 to 3 (Murphy et al 2008) identifies that anaemia is a common complication of CKD. The impairment of erythropoietin production in the kidneys leads to anaemia with signs and symptoms including fatigue, general malaise, angina, tachycardia and shortness of breath on exertion, especially in the absence of pulmonary or peripheral oedema.…”
Section: Anaemiamentioning
confidence: 99%
“…There are a number of international and country‐specific guidelines and standards that exist for the management of anaemia (Murphy et al 2008). NKF‐K/DOQI (2007) recommend that the selection of the haemoglobin (Hb) target and selection of the Hb level at which erythropoiesis stimulating agents (ESA) therapy is initiated for the individual patient should include consideration of potential benefits (including improvement in quality of life and avoidance of transfusion) and potential harms (including the risk of life threatening adverse events).…”
Section: Anaemiamentioning
confidence: 99%
“…Optimal outcomes for preserving kidney function and prevention of cardiovascular disease can only be achieved if patients are supported and encouraged in self‐managing their disease through support aimed at developing successful coping strategies for their lifelong medication regimen (De Geest et al 2005; Murphy et al 2008). Research has shown that knowledge and instruction alone is insufficient for effective self‐management (Van der Bijl 2001).…”
Section: Introductionmentioning
confidence: 99%
“…With regard to the aims, this literature review has highlighted that young people with CKD live with the actual or threatened loss or impairment of body functioning such as weight loss, weakness, lack of energy and impaired cognition. Youngsters with CKD can experience a loss of social interaction, loss of membership in groups, frustrations in their plans for the future, difficulties in school and academia as well as marked changes in their relationships to members of their family (Sand et al 1966; Scharer et al 1994; Watson 1996; Wong et al 2007; Murphy et al 2008a, 2008b; Watson et al 2010). Living with CKD (in particular stages 4 and 5), therefore, has consequences for young people in a number of dimensions, which transcend pathophysiological abnormalities, making coping with this chronic illness challenging (Heiwe et al 2003).…”
Section: Discussionmentioning
confidence: 99%